The Ubiquitin Conjugating Enzyme UbcD1 is Required for Notch Signaling Activation During Drosophila Wing Development - Zhang, Fengchao; Chen, Yao; Shen, Jie; Zhang, Junzheng (Frontiers in Genetics, 2021)
Notch signaling pathway plays crucial roles in animal development. Protein ubiquitination contributes to Notch signaling regulation by governing the stability and activity of major signaling components. Studies in Drosophila have identified multiple ubiquitin ligases and deubiquitinating enzymes that modify Notch ligand and receptor proteins. The fate of ubiquitinated substrates depend on topologies of the attached ubiquitin chains, which are determined by the ubiquitin conjugating enzymes (E2 enzymes). However, which E2 enzymes participate in Notch signal transduction remain elusive. Here, we report that the E2 enzyme UbcD1 is required for Notch signaling activation during Drosophila wing development. Mutations of UbcD1 lead to marginal nicks in the adult wing and reduction of Notch signaling targets expression in the wing imaginal disc. Genetic analysis reveal that UbcD1 functions in the signaling receiving cells prior to cleavage of the Notch protein. We provide further evidence suggesting that UbcD1 is likely involved in endocytic trafficking of Notch protein. Our results demonstrate that UbcD1 positively regulates Notch signaling and thus reveal a novel role of UbcD1 in development.